Coding Accuracy in Medical Records of Mental Health Patients at Prof. Hb. Saanin Mental Hospital, Padang - Mandia, Sayati; Nasution, Nurhasanah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Hospitals, in providing medical record services to support healthcare delivery, must maintain the quality of medical records. This requires completeness of medical information related to the patient's medical history, from the beginning of treatment to discharge. Diagnosis coding in medical records must be complete and accurate in accordance with ICD-10 guidelines. The accuracy of diagnosis and treatment codes significantly impacts the quality of statistical data and healthcare payment using a case-mix system. Inaccurate diagnosis codes will result in inaccurate data. Incorrect codes will result in incorrect rates. This study, analyzing the accuracy of coding in the medical records of mental health patients at Prof. Hb. Saanin Mental Hospital, Padang, aims to examine the accuracy of coding mental health diagnoses. This study employed descriptive research with quantitative methods and direct observation of medical records. This study was conducted in the Medical Records Unit of Prof. Hb. The study was conducted between February and April 2024. The population was the medical records of inpatients with mental health issues at Prof. HB. Saanin Mental Hospital, Padang, in 2022. The sample size for this study was 99 medical records, using simple random sampling. Data collection involved observation, checking the accuracy of the patient's medical records and using a checklist to categorize the medical records, with a value of 1 representing accurate and 0 representing inaccurate. Data analysis employed descriptive methods. The results showed that coding accuracy for mental illness cases was 90% accurate and 10% inaccurate. The most common inaccurate diagnosis was mixed-type schizophrenia.